Urinary Incontinence and Pelvic Organ Prolapse Knowledge, Care-Seeking, and Embarrassment in Women Planning Bariatric Surgery: A Cross-sectional Study. Issue 4 (April 2020) - Paka, Chandhana; Hallock, Jennifer L.; Trock, Bruce; Steele, Kimberley; James Wright, E.
Abstract : Objective: The objective of this study was to assess whether patients seeking bariatric surgery were at least as proficient in urinary incontinence (UI) and pelvic organ prolapse (POP) knowledge as the general population. Our secondary objective was to determine care-seeking and impact of embarrassment on knowledge of pelvic floor disorders (PFDs). Methods: An anonymous survey was administered to adult women who attended a bariatric surgery information session from May 2015 to January 2016. The comprehensive survey included multiple data points and the Prolapse and Incontinence Knowledge Quiz. The study population was compared with a general population described in a previously published study. Results: Three hundred fifteen participants completed the survey (88% response rate). Mean ± SD age was 41.1 ± 11.3 years (range, 18–69 years), and mean body mass index was 47.4 ± 9.6 kg/m 2 (range, 26.7–104.5 kg/m 2 ). A total of 196 women (62.2%) had at least one bothersome PFD symptom. The study population was at least as proficient in UI knowledge as the general population ( P < 0.0001), but not for POP knowledge ( P < 0.946). Among participants with symptomatic PFD, 91.7% of those with UI symptoms and 70% of those with POP symptoms reported that they would seek care. There was a difference in knowledge proficiency between women who were and were not embarrassed to discuss UI ( P = 0.77) or POP ( P = 0.99). Conclusions: The study population demonstrated less POP knowledge than the general population, but not for UI knowledge. A high proportion of women with UI or POP symptoms would seek care, but embarrassment to discuss UI or POP negatively impacted knowledge.